( f ( x + y ) ) 2 ≥ ( f ( x ) ) 2 + ( f ( y ) ) 2 for all x , y ∈ R .
Let f : R ↦ R be a function that satisfy the condition above.
Evaluate f ( 2 0 1 6 ) .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
You are claiming the only function which meets the condition is f(x)=0 ...?
Let f be the identity function, then it satisfies your inequality, right?? So the answer is not unique...
Log in to reply
No, the identity function doesn't satisfy this condition. Take x = 1 , y = − 1 to see why.
Log in to reply
The notation f 2 ( x ) means f ( f ( x ) ) ,doesn't it?
If f is the identity then f^2 is also the identity function and so we just get x+y >= x+y which is always true...
I guess the problem meant to say ( f ( x ) ) 2 instead of f 2 ( x ) ...?
Log in to reply
@Nathanael Case – Its multiplication, not composition.
Problem Loading...
Note Loading...
Set Loading...
If x = 0 , then f 2 ( 0 ) ≥ f 2 ( 0 ) + f 2 ( 0 ) ⇒ 0 ≥ f 2 ( 0 ) .
If y = − x , then 0 ≥ f 2 ( 0 ) = f 2 ( x − x ) ≥ f 2 ( x ) + f 2 ( − x ) .
Since f 2 ( x ) ≥ 0 for all x ∈ R , it implies that f 2 ( x ) = 0 and f ( x ) = 0 for all x ∈ R